Tracing Eastern Influences in The Fakeer of Jungheera - Dr. Goswami Shivdani Giri, (The Creative Launcher, 2021)
The paper aims at analysing various influences that Henry Derozio underwent in the composition of his Fakeer of Jungheera. The reviewers and commentators, while admitting some poetic merits in the poem, find it largely imitative of Byron and hence greatly wanting. However, a close first-hand study of the poem along with the poet’s notes alluded to it throws light on a number of facts related to its subject matter and style. It is revealed that far from being modelled on Byron's ballads like The Corsair or The Siege of Corinth or The Prisoner of Chillon, it is unmistakably Indian in conception and amazingly rich in local colours and imagery. Even the apparent similarity is superficial, and instead of being a fanciful tale, the Fakeer of Jungheera is the poetic recreation of a real-life episode heard by and believed in by the poet. The paper also examines the art of poetic diction and devices that the poet employs in the poem.